Clinical courses, impact and prognostic indicators for a persistent course of low back pain: Results from a population-based cohort study - Gomes, LA (2023)
Background: Low back pain (LBP) is a long-term health condition with distinct clinical courses. Its characterization together with the identification of prognostic factors for a persistent LBP course may trigger the development of personalized interventions. This study aimed to investigate the courses of chronic LBP (CLBP), its cumulative impact, and the indicators for the persistence of pain. Material and methods: Patients with active CLBP from the EpiDoC, a population-based cohort study of a randomly recruited sample of 10.661 adults with prolonged follow-up, were considered. Pain, disability, and health-related quality of life (HRQoL) were assessed at three time-points over five years. According to their pain symptoms over time, participants were classified as having a persistent (pain at the baseline and at all the subsequent time-points) or a relapsing pain course (pain at the baseline and no pain at least in one of the subsequent time-points). A mixed ANOVA was used to compare mean differences within and between patients of distinct courses. Prognostic indicators for the persistent LBP course were modulated through logistic regression. Results: Among the 1.201 adults with active CLBP at baseline, 634 (52.8%) completed the three time-points of data collection: 400 (63.1%) had a persistent and 234 (36.9%) a relapsing course. Statistically significant interactions were found between the group and time on disability (F (2,1258) = 23.779, p<0.001) and HRQoL (F (2,1252) = 82.779, p<0.001). In the adjusted model, the persistent course was associated with the disability level (OR 1.86, CI95% 1.40-2.40, p<0.001), depressive symptoms (OR 1.96, CI95% 1.21-3.18, p = 0.007), female gender (OR 1.90, CI95% 1.26-2.87, p = 0.002) and having a manual job (OR 1.46, CI95% 1.02-2.10, p = 0.040). Conclusion: In the long-term, patients with CLBP may follow a persistent or relapsing course of pain. Being female, presenting depressive symptoms, having a manual job and higher disability at baseline predicts a persistent course of LBP.